Foundation of Ethics and Practice in Amitābha Cult: Modern Social Perspective (International Journal of Engineering and Computer Science, 2017)
Ethics is one of the most important areas of philosophy which is studied and analyzed not only in science but also in religion. The value and benefit of ethics can help one to have good relation between the members of society. The aim of secular ethics is to teach us how to live, work and treat others in the best way. The aim of religious ethics is to help us become not only a good man in this life but also attain holiness in the present time, and the future one. Therefore, ethics is very important in any religious teaching. Each religious teaching has its own ethical theory which stresses the important of ethics for attaining the final goal. In this paper, I will discuss about the Buddhist ethical theory and its practical application in the Amitābha Cult.